Respuesta :
Function transformation involves changing the form of a function.
f(x) is transformed to g(x) by (a) -2f(x + 4)
The function is given as:
[tex]f(x) = \sqrt[5]{x}[/tex]
Start by shifting f(x) to the left by 4 units.
The rule of this transformation is:
[tex](x,y) \to (x + 4,y)[/tex]
So, we have:
[tex]f(x + 4) = \sqrt[5]{x + 4}[/tex]
Next, the function is stretched by a factor of 2.
The rule of this transformation is:
[tex](x,y) \to (x,2y)[/tex]
So, we have:
[tex]2f(x + 4) = 2\sqrt[5]{x + 4}[/tex]
Rewrite as:
[tex]g(x) = 2\sqrt[5]{x + 4}[/tex]
The above function passes through the points (-5, 2), (-4, 0), (-3, -2) and (4, -3)
Hence, f(x) is transformed to g(x) by -2f(x + 4)
Read more about function transformation at:
https://brainly.com/question/1548871